FAKTOR-FAKTOR YANG MEMPENGARUHI TARGET PENJUALAN STUDI KASUS PADA GROSIR CAHAYA ASIA MEDAN - Zainarti Zainarti; Sarah Febrian; Syahfitri Ronauli Daulay; Ridho Maulana Kombih (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
. The purpose of this research is to identify and analyze the factors that influence the sales targets of Wholesale Cahaya Asia Medan. This research uses a qualitative approach with case studies to explore the factors that influence sales targets at Wholesale Cahaya Asia Medan, which was chosen as the research location because of its large volume. high and diverse products. This research data consists of primary data and secondary data. Primary data includes participant observation, where researchers directly observe sales activities, interactions between employees and customers, as well as other factors that influence sales, and in-depth interviews with store owners, sales managers, employees, and customers to reveal marketing strategies, customer satisfaction, competition market, and economic conditions. Based on the results of this research, it can be concluded that there are several internal and external factors that influence the sales targets of Cahaya Asia Medan Wholesalers. Internal factors include stock availability, employee capabilities, and management systems. External factors include economic conditions, competition, and natural disasters. Wholesale Cahaya Asia Medan can implement several strategies to increase sales, such as improving product and service quality, expanding market reach, increasing promotions and marketing, and utilizing technology. Keywords: target, sales, wholesale.